Psychosomatic Manifestations in Speech and Language Disorders: A Comprehensive Review - Saadat, Maryam; Sheydaei, Hajieh; Kia kojori, Razie; Ghasemzadeh, Azizreza (Journal of Personality and Psychosomatic Research (JPPR), 2023)
This review explores the interplay between psychosomatic factors and speech and language disorders, highlighting the importance of a holistic approach in diagnosis and treatment. To systematically review the literature on psychosomatic aspects in speech and language disorders and to discuss the implications for clinical practice. A comprehensive search of databases including PubMed, PsycINFO, and others was conducted. Studies focusing on the psychosomatic aspects of speech and language disorders published in English from 2000 onwards were included. The review identified a significant interrelation between psychological well-being and speech and language disorders. It emphasized the need for integrating psychological assessment in speech-language pathology and discussed various therapeutic interventions that address both speech-language and psychological aspects. The findings underscore the necessity of considering psychosomatic factors in the assessment and treatment of speech and language disorders. The review suggests the integration of multidisciplinary approaches for effective management.